A sequential mediation model linking workplace environment and work well-being via job resources and burnout among trainers in Malaysia’s Ministry of Health Training Institutes - Muhamad Nasharudin, Nurfazreen Aina; Jiakai, Liu; Suhaimi, Nur Afirah (Discover, 2026)
Background: Work well-being has become a critical concern in healthcare and educational sectors, yet limited research has examined how workplace conditions influence work well-being among health trainers in Malaysia. This study aimed to explore the sequential mediating roles of job resources and burnout in the relationship between workplace environment and work well-being among trainers in the Ministry of Health Training Institutes. Method: A cross-sectional survey was conducted among 651 trainers from 19 ILKKM campuses across Malaysia. Validated instruments were used to assess workplace environment, job resources, burnout, and work well-being. Data were analyzed using Hayes’ PROCESS macro (Model 6) with 5,000 bootstrap samples to test the sequential mediation model. Results: The findings revealed that workplace environment positively predicted job resources and negatively predicted burnout, both of which showed statistically significant but modest effects on work well-being. The indirect effects through job resources, burnout, and their sequential pathway were statistically significant. The model explained 39.8% of the variance in work well-being, indicating satisfactory explanatory power. Conclusions: A supportive workplace enhances job resources, reduces burnout, and improves trainers’ work well-being. The results provide evidence for the dual pathways of the Job Demands–Resources framework, in which motivational processes strengthen engagement while strain processes are mitigated through adequate resources. Strengthening organizational support and cultivating participative and resourceful work climates may foster sustainable work well-being among healthcare trainers in Malaysia.